Cellular uptake of BCG-loaded chitosan microparticles and in vivo evaluation of immune response following intranasal immunisation - Caetano, Liliana Aranha (2013)
Attenuated Mycobacterium bovis bacillus Calmette-Guérin (BCG) is the only currently available vaccine against tuberculosis. It is highly effective in pre-exposure immunisation against TB in children when administered by subcutaneous route to newborns. However, it does not provide permanent protection in adults. In this work, polymeric chitosan-alginate microparticles have been evaluated as potential nasal delivery systems and mucosal adjuvants for live attenuated BCG. Chitosan (CS) has been employed as adjuvant and mucosal permeation-enhancer, and, together with alginate (ALG), as additive to enhance BCG-loaded microparticles (MPs) cellular uptake in a human monocyte cell line, by particle surface modification. The most suitable particles were used for vaccine formulation and evaluation of immune response following intranasal immunisation of BALB/c mice.